Gallstone ileus with an enterovaginal fistula: a rare complication of pelvic radiotherapy - Wali, Luqman (BJR Case Rep, 2020)
Gallstone ileus is a rare cause of small bowel obstruction. Chronic gallstone irritation can lead to the formation of a cholecystoduodenal fistula, with gallstone impaction typically in the terminal ileum. Rarely gallstones can become impacted in other structures such as the colon or can even erode through the bowel. We present an unusual case of a gallstone ileus which resulted in the formation of an enterovaginal fistula, secondary to previous pelvic radiotherapy. Our case highlights the importance of considering fistula formation as a late complication of radiotherapy and how this can alter expected features of other pathologies, such as a gallstone ileus.